Tobacco Use Among College Students Across Various Disciplines in Kerala, India. (July 2020) - Menon, Priya G; George, Sanju; Nair, B Sivasankaran; Rani, Anjana; Thennarasu, K; Jaisoorya, TS
Background: Tobacco use is a major public health concern in India. Its use in young people is linked to increased severity, longer duration, and reduced efforts to seek treatment for tobacco use. A significant proportion of young people are enrolled in colleges, and early prevention during this period has better effectiveness. There is preliminary evidence that prevalence may vary across courses even among students of the same sociocultural background. Hence, we compared the prevalence and correlates of tobacco use among college students enrolled in five common streams of collegiate education (medical, nursing, engineering, arts/science and others, law/fisheries) in Kerala, India. Methods: 5784 college students from 58 colleges (medical, nursing, engineering, arts, and law and fisheries) selected by cluster random sampling in the district of Ernakulum, Kerala, completed a self-administered questionnaire incorporating standardized instruments. R software was used for analyses. Lifetime prevalence and severity of tobacco use were determined. Sociodemographic variables of tobacco users and nonusers enrolled in various courses were compared using chi-square test and two-way ANOVA. Furthermore, for each course, factors influencing tobacco use were identified using multivariable logistic regression analysis. Results: The mean age of the sample was 19.5 ± 1.9 years, with the majority being female (65.3%). Lifetime prevalence of tobacco use varied from 0.5% in nursing students, 4.2% in medical students, 8.2% in students of arts and science, 12.5% in engineering students, and 22.8% among other students (law/fisheries). Approximately two-thirds of all tobacco users across courses showed signs of nicotine dependence. Dependent users also showed variance with none in nursing, 2.6% among medicine, 1.6% among arts and science, 1.9% among engineering, and 6.3% among others. Male gender and alcohol use were consistently associated with tobacco use across courses, whereas other examined psychosocial correlates showed variance. Conclusions: To conclude, it appears that among college students, course-level characteristics may influence risk of tobacco use. This has public health importance as it suggests that interventions need to be tailored bearing this in mind. Future research needs to examine campus-level characteristics that may explain variance.